2001
DOI: 10.1107/s0909049500015958
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of (NH4)2[PdCl6] studied by in situ X-ray absorption spectroscopy

Abstract: In situ X-ray absorption near edge structure (XANES) investigations were carried out at chlorine K edge and palladium L3 edge to study the mechanism of the thermal decomposition of ammonium hexachloropalladate. The spectra show a characteristic feature for the initial step that might be explained as the formation of the precursor via ligand exchange (Cl --> NH3). Multiple scattering calculations (Feff 8) for the Cl K, Pd and Rh L3 edges were successful in simulating the XANES spectra of the precursor as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The time domain for chemically or thermally driven reactions could vary from hours to ultrafast regime when atomic or electronic motions are the dominant effect. Representatives are catalytic process7, formation of metal nanoparticles89 and thermolysis dynamics1011 and such reactions are well suited for time-resolved EDE studies.…”
mentioning
confidence: 99%
“…The time domain for chemically or thermally driven reactions could vary from hours to ultrafast regime when atomic or electronic motions are the dominant effect. Representatives are catalytic process7, formation of metal nanoparticles89 and thermolysis dynamics1011 and such reactions are well suited for time-resolved EDE studies.…”
mentioning
confidence: 99%
“…The main peak at 2828.8 eV shifts to 2827.4 eV after dissolving Lcysteine into the Rh(PVP) nanocolloidal solution and the peak intensity at 2827.4 eV increases with the reaction time. Rumpf et al and Sugiura et al have reported that the peak at around 2827.4 eV can be observed in the Cl K-edge NEXAFS spectra for the specimen of ammonium hexachlororhodate(III) complex [(NH 4 ) 3 [RhCl 6 ]] [13,14]. Since this same complex structure cannot exist due to steric repulsions on the Rh nanoparticle surface, it is thought that similar structure is produced on the Rh nanoparticle surface in the mixed sample.…”
Section: B CL K-edge Nexafs Measurementmentioning
confidence: 99%
“…Previous TG (thermogravimetric) data collected in an inert atmosphere for (NH 4 ) 2 [MCl 6 ] salts with Ir, Re and Os did not suggest the formation of any intermediates in the following stoichiometric reaction: 11 3(NH 4 ) 2 [MCl 6 ] -3M + 2N 2 + 16HCl + 2NH 4 Cl (1) Thermal decomposition of Pt and Pd (NH 4 ) 2 [MCl 6 ] salts seems to be particularly complicated. In situ XAFS experiments with (NH 4 ) 2 [PdCl 6 ] at Cl K-and Pd/Rh L 3 -edges 12 suggested the formation of several intermediates such as Pd(NH 3 )Cl 5 , trans-Pd(NH 3 ) 2 Cl 2 or (NH 4 ) 2 [PdCl 4 ]. A similar experiment with (NH 4 ) 2 [PtCl 6 ] 13 revealed a fingerprint of cis-Pt(NH 3 ) 2 Cl 2 , however, by considering some other platinum amine complexes as intermediates.…”
Section: Introductionmentioning
confidence: 99%